Contact mechanics of half-space with micro-structures - Muhammad Nabil Bin Abdul Rahim (Nanyang Technological University, 2024)
The study of contact mechanics has traditionally focused on stress distributions within a uniform half-space. However, in industries dealing with micro and nano-scale devices, understanding contact mechanics in a non-uniform half-space has become increasingly relevant. This project explores the contact stress behaviour in non-uniform half-space using finite element analysis (FEA) implemented through ANSYS. By modelling micro-structured surfaces and their interactions with contact indentors of varying geometric shapes and dimensions, this study aims to provide new insights into the mechanical behaviour of non-uniform and rough surfaces. The findings have significant implications for the design and optimization of micro and nano-scale devices, where accurate surface property detection is crucial. This Final Year Report evaluates the contact mechanics of a half-space with micro-structures. A finite element scheme is used to develop a micro-mechanics model for rough surface contact with varying profiles and asperities (surface roughness or irregularities). The dimensionless average real pressure is obtained as a function of the ratio of the real contact area to the apparent contact area (A0 / An). The finite element method (FEM), implemented in ANSYS, is employed to study the contact behaviour between two materials: polymer and structural steel. These materials were selected based on their differing Young’s modulus ratios while maintaining the same Poisson’s ratio.